Biological Nitrogen Removal by A Membrane-Aerated Biofilm Reactor: An Attempt to Treat Urine Wastewater with High Sustainability. Issue 1 (1st June 2022) - Zhan, Chengbo; Zhang, Liangchang; Ai, Weidang; Dong, Wenyi
Abstract: Human urine contains the majority of nutrients in domestic wastewater, therefore treatment of source-separated urine by sustainable methods would become a low-cost and eco-friendly alternative to conventional urban wastewater treatment system. In this work, a waste stream composed of real urine and hygiene wastewater was prepared, which had characteristic of high nitrogen content and low available C/N ratio. Membrane-aerated biofilm reactor (MABR) is an emerging technology utilizing microporous or nonporous aeration membranes as the substrate for biofilm attachment, and this configuration could promote the growth of autotrophic nitrifying bacteria and the efficiency of nitrogen removal process. The waste stream was treated with a home-made MABR system to remove the organic carbon and nitrogen pollutants. Over a four-month operation period with the incoming waste stream concentration progressively elevated, the system achieved 90-95% removal of TOC, 50-73% oxidation of ammonium-nitrogen, and 24-63% removal of total nitrogen from the influent, without external carbon source input. The results indicated that MABR has the potential for urine wastewater treatment with low consumption in energy and materials.